Phosphate accumulation in rice leaves promotes fungal pathogenicity and represses host immune responses during pathogen infection - Martín-Cardoso, Héctor; Bundó, Mireia; Val-Torregrosa, Beatriz; San Segundo, Blanca (Frontiers in Plant Science, 2024)
Rice is one of the most important crops in the world and a staple food for more than half of the world's population. Blast disease caused by the fungus Magnaporthe oryzae poses a severe threat to food security through reduction of rice yields worldwide. High phosphate fertilization has previously been shown to increase blast susceptibility. However, our knowledge on the mechanisms underpinning phosphate-induced susceptibility to M. oryzae infection in rice is limited. Here, we conducted live cell imaging on rice sheaths inoculated with a M. oryzae strain expressing two fluorescently-tagged M. oryzae effectors. We show that growing rice under high phosphate fertilization, and subsequent accumulation of phosphate in leaf sheaths, promotes invasive growth of M. oryzae. Consistent with this, stronger expression of M. oryzae effectors and PMK1 occurs in leaf sheaths of rice plants grown under high a phosphate regime. Down-regulation of fungal genes encoding suppressors of plant cell death and up-regulation of plant cell death-inducing effectors also occurs in sheaths of phosphate over-accumulating rice plants.Treatment with high Pi causes alterations in the expression of fungal phosphate transporter genes potentially contributing to pathogen virulence. From the perspective of the plant, Pi accumulation in leaf sheaths prevents H2O2 accumulation early during infection which was associated to a weaker activation of RBOHs genes involved in ROS production. Further, a weaker activation of defense-related genes occurs during infection in plants over-accumulating phosphate. From these results, it can be concluded that phosphate fertilization has an effect on the two interacting partners, pathogen and host. Phosphatemediated stimulation of fungal effector genes (e.g., potentiation of fungal pathogenicity) in combination with repression of pathogen-inducible immune responses (e.g., ROS accumulation, defense gene expression) explains higher colonization by M. oryzae in rice tissues accumulating phosphate. Phosphate content can therefore be considered as an important factor in determining the outcome of the rice/M. oryzae interaction. As fertilizers and pesticides are commonly used in rice cultivation to maintain optimal yield and to prevent losses caused by pathogens, a better understanding of how phosphate impacts blast susceptibility is crucial for developing strategies to rationally optimize fertilizer and pesticide use in rice production.